Krest'ianskii vopros . Krest'ianskii vopros . The Peasant Question . Крестьянский вопрос - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Alexandr Rutskoi meets with the leaders of the striking enterprises. Series description: Information and analytical program on agriculture, and the life and work of farmers and peasants. Broadcasted on television in the first half of the 1990s. Встреча Руцкого А.В. с руководителями бастующих предприятий. Описание серии: Информационно-аналитическая программа о жизни и работе крестьян и фермеров. Транслировалась на телевидении в первой половине 1990-х годов.